Pengaruh Penggunaan Media Pembelajaran Augmented Reality (AR) Terhadap Hasil Belajar Siswa Tentang Ekosistem Di Kelas III SD Inpres Noelbaki Kabupaten Kupang - Miha Balo, Joyvinitra; R. Koroh, Taty; Bon Nifu Benu, Adam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to test the significant influence of the use of Augmented Reality technology-based learning media on the learning outcomes of third-grade students on Ecosystem material in third-grade SD Inpres Noelbaki, Kupang Regency. The type of research used is quantitative experimental research. The population in this study were third-grade students of SD Inpres Noelbaki with the research sample being students of class III C. Data were obtained through observation and testing, which were then analyzed in two stages, namely test analysis in the form of validity and reliability tests, then data analysis in the form of normality tests, homogeneity tests and hypothesis tests. The results of the study showed a significant influence of Augmented Reality learning media on student learning outcomes, this was indicated by an increase from the pretest to the posttest results and the results of the hypothesis test stating that H_0 was rejected and H_a was accepted with a significance level obtained of 0.000 <0.05.